Effective Policing for 21st-Century Israel - Jessica Saunders, Steven W. Popper, Andrew R. Morral, and Robert C. Davis (RAND Corporation, 2013)
past two decades. There is a public interest in having the police provide a type and level of service that keeps pace with these changes. Despite relatively low crime rates, the public in Israel perceives an increasing threat to personal security and concern over quality of police service. The Ministry of Public Security, the Ministry of Finance, and the Israel Police asked the RAND Corporation to conduct a study that would help these organizations address several issues of mutual concern. They requested that RAND address issues of public perceptions and public trust in the police, in terms of benchmarking the police against other police organizations, performance measurement, and deterrence and crime prevention. This document reports the outcome of the resulting two-year project. The project was jointly funded by the government of the State of Israel and with the generous support of donors to RAND’s Israel Public Policy Fund, most notably the Younes and Soraya Nazarian Family Foundation, without whose assistance this project would not have been possible. RAND also benefited from generous support by the Rosalinde and Arthur Gilbert Foundation, the Glazer Family Foundation, and Mr. Stanley Gold. This report should be of interest to the public, civil society organizations, and the government of the State of Israel, as well as to those with a general interest in policing policy, police governance, performance measurement, and police-community relations. The study represents one of a series of studies produced by RAND for the benefit of the people and government of Israel as part of RAND’s Israel Initiative.